3x-1=3(x+5)

Simple and best practice solution for 3x-1=3(x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-1=3(x+5) equation:


Simplifying
3x + -1 = 3(x + 5)

Reorder the terms:
-1 + 3x = 3(x + 5)

Reorder the terms:
-1 + 3x = 3(5 + x)
-1 + 3x = (5 * 3 + x * 3)
-1 + 3x = (15 + 3x)

Add '-3x' to each side of the equation.
-1 + 3x + -3x = 15 + 3x + -3x

Combine like terms: 3x + -3x = 0
-1 + 0 = 15 + 3x + -3x
-1 = 15 + 3x + -3x

Combine like terms: 3x + -3x = 0
-1 = 15 + 0
-1 = 15

Solving
-1 = 15

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -1/8(24x-56)= | | (4/a)^-3 | | 35-7x=5 | | h=16t^2+8t+96 | | Ax+fy=k | | 9y^2-16y=0 | | 18y^2-33y+10=0 | | 9n-18=-4+2n | | 5y-6=-30+y | | -2y+3=4y+6 | | x^(-1/2)=2/3 | | 3.3x-32=2.5x+4 | | n=1.96 | | 5u^2=-13u-6 | | X(.2)=900 | | h=-16t^2+50t+448 | | 20x+7-5x=5x-7 | | x+39+x+7=8 | | 2/5-7(5.4) | | x(x+5)(x+7)(x+12)+150=0 | | 15+12=a | | 16x+22-2x=2x-22 | | 23+2x+6-5x=8 | | m^2+54=0 | | 16x+6-4x=4x-6 | | (9/4)-(y^2/5)=1 | | 4x^2+3=x+9 | | y=20-x/4 | | 4y+2=12-y | | 2x-1=(4x+3) | | x+(x+2)=6x | | 10y=7y-15 |

Equations solver categories